Estimates Of Russia’s Potential Output - Janíčko, Martin; Maleček, Petr; Janíčko, Pavel (Ekonomika, 2021)
Taking into consideration the specifics of the Russian economy such as dependency on oil and gas drilling & production, and including the current context of the Western sanctions, COVID-19 pandemic, as well as somewhat idiosyncratic potential output development, the main aim of this paper is to quantify recent output gap for Russia. We use three mainstream methodologies: the Hodrick-Prescott filter as a benchmark, the Kalman filter to follow, and the Cobb-Douglas production function. The sample time span ranges from 1995Q1 until 2020Q3, while all calculations are performed on quarterly frequencies. The analysis suggests that given low fixed investment ratios, limited R&D spending in non-military sectors, and adverse demographic development, under a “no policy change” scenario there might soon be even more downward pressures on the country’s potential output growth, and the economy may continue increasing only at a snail’s pace even after a possible withdrawal of the Western sanctions and the end of the COVID-19 pandemic.